2011
DOI: 10.1016/j.compedu.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparing e-Learning tools’ success: The case of instructor–student interactive vs. self-paced tools

Abstract: E-learning tools have profoundly transformed modern pedagogical approaches. Vendors provide different types of systems, such as self-paced (SP) and instructor-student interactive (ISI) elearning tools. Although both types of tools represent promising solutions to facilitate the learning process, it is important to theoretically identify a framework to evaluate the success of these tools and assess whether one type of tool is more effective than another. Toward this end, we (1) propose a model to evaluate e-lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 70 publications
1
31
0
Order By: Relevance
“…The findings are consistent with the Islam's () argument that satisfaction with the environment and content has a high positive correlation with students' perceived academic performance. Similar results were reported in previous studies, where satisfaction is an important antecedent of perceived academic performance (Lee & Lee, ; Cho & Hsieh, ) and perceived learning effectiveness (Liaw, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings are consistent with the Islam's () argument that satisfaction with the environment and content has a high positive correlation with students' perceived academic performance. Similar results were reported in previous studies, where satisfaction is an important antecedent of perceived academic performance (Lee & Lee, ; Cho & Hsieh, ) and perceived learning effectiveness (Liaw, ).…”
Section: Discussionsupporting
confidence: 91%
“…Students meeting the required goals in terms of higher grades predict their satisfaction from the learning environment or content. Satisfied users perform better than unsatisfied users (Bailey & Pearson, ; Lee & Lee, ; Cho & Hsieh, ). Islam () argued that if the students are provided with better learning assistance in terms of learning content and effective discussions, they become satisfied with the content and overall learning environment, which leads to improved academic performance.…”
Section: Research Frameworkmentioning
confidence: 99%
“…the ability to propose several possibilities or solutions for one question. A student's thinking presents fluency when proposing several responses at the stage of concept generation (Hsieh et al, 2011). 2.…”
Section: Creativitymentioning
confidence: 99%
“…One of the key determinants identified in their work was flexibility. Hsieh and Cho (2011) used TAM to compare instructor-to-student interactive versus self-paced e-learning tools, and their findings indicated that instructor-to-student interactive e-learning tools led to higher perceived usefulness and learning outcomes.…”
Section: Introductionmentioning
confidence: 99%